Effect of the longitudinal trim of KCS container ship on its resistance at different speeds - Nassif, Boushra (Latakia University Journal -Engineering Sciences Series, 2025)
In this research, CFD technique was used to study the effect of the longitudinal trim of a container ship KCS on its resistance at a constant draft and at different values ​​of ship speed. The URANS method and the k-omega SST turbulence model were used to solve the Navier-Stokes equations. The study was carried out at the following longitudinal trim angles -0.8, -0.6, -0.4, -0.2, -0.1, 0, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2 and at each angle the calculations were carried out at three values ​​of Froude number which are 0.108, 0.195, 0.282. Both the ship's draft and its scale were fixed. The study was conducted on the scale model due to the availability of a large number of experimental results for this model, which were used to validate both the grid and the numerical settings. Therefore, the calculations were initially performed for several cases that were completely identical to the experimental cases, and the numerical results were compared with the available experimental results, and the agreement between the results was very good. In the next step, the effect of the longitudinal trim angle on the ship's resistance was studied at different speed values. The results obtained confirmed that at low ship speeds, the effect of the trim angle is negative and does not help in reducing the resistance, and with increasing ship speed, the positive effect of the longitudinal trim angle appears in reducing the ship's resistance. The results also confirmed that the negative trim angle (in which the bow draft is greater than the stern draft) negatively affects the resistance, unlike the positive trim angle, which helps in reducing the ship's resistance.